2016
DOI: 10.1016/j.bj.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Current and future alternative therapies for beta-thalassemia major

Abstract: Beta-thalassemia is a group of frequent genetic disorders resulting in the synthesis of little or no β-globin chains. Novel approaches are being developed to correct the resulting α/β-globin chain imbalance, in an effort to move beyond the palliative management of this disease and the complications of its treatment (e.g. life-long red blood cell transfusion, iron chelation, splenectomy), which impose high costs on healthcare systems. Three approaches are envisaged: fetal globin gene reactivation by pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 200 publications
0
63
0
14
Order By: Relevance
“…Several new treatment modalities including fetal globin gene reactivation, allogeneic haematopoietic stem cell transplantation (alloHSCT) and gene therapy are being explored to correct the disparity in α/β globin chains in thalassaemia (de Dreuzy et al , ). Fetal haemoglobin (HbF) expression could decrease ineffective erythropoiesis by reducing the build‐up and precipitation of α‐globin chains (Soni, ).…”
Section: Clinical Characteristics Change Of Hb (G/l) and Transfusionmentioning
confidence: 99%
“…Several new treatment modalities including fetal globin gene reactivation, allogeneic haematopoietic stem cell transplantation (alloHSCT) and gene therapy are being explored to correct the disparity in α/β globin chains in thalassaemia (de Dreuzy et al , ). Fetal haemoglobin (HbF) expression could decrease ineffective erythropoiesis by reducing the build‐up and precipitation of α‐globin chains (Soni, ).…”
Section: Clinical Characteristics Change Of Hb (G/l) and Transfusionmentioning
confidence: 99%
“…The application of bio-psychosocial model in thalassemia can interpret the biological factors related to the thalassemia in the context of genetic vulnerability, disability and physical health while social factors includes awareness and knowledge about the disease and cultural practices for the understanding and propagation of thalassemia. Reviewing the literature showed that psychological aspects are only measured as impact of thalassemia on patients and their families (Baraz et al, 2016;Behdani et al, 2015;Mansoor et al, 2018), however genetic abnormalities (Brancaleoni et al, 2016;de Dreuzy et al, 2016) and socio-cultural factors (Sarvestani et al, 2019;Seyedifar et al, 2016) are the major risk factors of thalassemia propagation.…”
Section: Theoretical Construction Of Beta Thalassemia Majormentioning
confidence: 99%
“…However it is still limited in developing countries because of the lack of equipment and the very expensive cost. [45]. This has been formalized by the classification Lucarelli who, depending on the presence or not of the 3 Risk factors that are hepatomegaly, portal fibrosis and insufficient chelation, classifies patients into three risk classes for transplant success [46] ( (class 1= no risk factor, class 2 =one or two risk factors and class 3= three risk factors).…”
Section: Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%